Pengaruh Intellectual Capital dan Struktur Modal Terhadap Return Saham Dengan Kinerja Keuangan Sebagai Variabel Intervening (Studi pada Perusahaan Yang Terdaftar pada JII (Jakarta Islamic Index) Periode 2012-2016) - Marlinda, Yefi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Intellectual capital is the company's wealth that is the power behind the company's value creation that includes knowledge, experience, skills, reputation, and also technological capabilities. Capital structure relates to sources of funds, both internal and external. The main purpose of this research is to investigate the relationship between intellectual capital and capital structure on stock return with financial performance as intervening variable. This type of research is quantitative research. The sample of this study is the annual financial statements of companies registered on JII (Jakarta Islamic Index) on period 2012-2016). The sample‟s were chosen by using purposive sampling method and 11 companies were able to fulfill the sample‟s criteria. The research data were analyzed by using path analysis method. The result of this research reported that there is indirect influence between intellectual capital and capital structure to stock return through financial performance measured by return on equity. Intellectual capital insignificance to indirect effect on stock return through financial performance measured through earning per share but there is indirect influence between capital structure on stock return through financial performance measured through earning per share. The study also found that intellectual capital insignificance on stock return. But the finding of direct influence between capital structure on stock return. From these findings it can be concluded that intellectual capital and capital structure indirect significance on stock return through financial performance measured through return on equity.